Detection of Molluscum contagiosum virus (MCV) subtype I as a single dominant virus subtype in molluscum lesions from a Turkish population - Saral, Y; Kalkan, A; Ozdarendeli, A; Bulut, Y; Doymaz, MZ (Elsevier Science Inc, 2006)
Background. Molluscum contagiosum has a worldwide occurrence and its primary mode of transmission is via direct human contact including sexual means. The aim of the study was to implement a polymerase chain reaction-based assay for detection and subtyping of Molluscum contagiosum virus (MCV) in skin lesions diagnosed with molluscum contagiosum in a large regional teaching hospital in Turkey. Methods. For this purpose, a total of 61 patients were included in the study. Randomly selected single lesion from each patient was used to extract DNA material and a specific PCR reaction amplifying 393-bp- and 575-bp-long regions from MCV genome was used in the detection. aubtyping was carried out by digestion of the amplified 575-bp product with restriction endonuclease enzyme BamH1. Both amplified and restriction enzyme digested products visualized on agarose gel electrophoresis. Results. All 61 molluscum cases (100%) included in the study contained MCV genetic material as demonstrated by the presence of 393- and 575-bp-long PCR amplified products. Restriction enzyme BamHI digestion of the 575-bp-long amplicon indicated that the infecting subtype in all the cases (100%) was MCV subtype I. Conclusions. Results of this study demonstrate that subtype I is the only infecting strain dominant in our region. Because the only consecutive molluscum patients admitted to our hospital were included in the study, our data do not rule out the possibility that other genotypes might be present in the Turkish population. However, it is not unreasonable to conclude that similar trends exist in the rest of the country. Results also show that a molecular-based diagnostic assay would be feasible in cases where diagnosis was deemed necessary. (c) 2006 IMSS. Published by Elsevier Inc.
Keywords: Molluscum contagiosum virus; subtype; Turkish population; PCR